Facial aesthetic preferences among ethnicity in Malaysia - Ismail, Adibah Hanim; Abdul Rashid, Muhammad Farhan; Mohd Zaman, Ungku Mohd Shahrin; Suparji, Noor Shahirah; Mohd Shahrol, Nur Izzati; Md Hatah, Ernieda; Qi, Hao Looi (Korean Society of Korean Cosmetic Surgery and Medicine, 2023)
Background: Malaysians, known for their diverse ethnicities, exhibit unique aesthetic features influenced by cultural nuances. Research indicates that factors including ethnicity, culture, and personal experiences affect how people perceive beauty. Objective: This study aims to address the lack of data on the preferred facial aesthetics among women from different ethnic groups in Malaysia. Methods: A questionnaire was administered to 290 Malaysian women, covering multiple regions and dimensions of facial aesthetics, including facial shape, forehead height and slope, cheekbone height, chin shape, eye region features (eyebrow shape, eyelid creases, and inner eye fold), nose (nose bridge shape, nasolabial angle, and nose width-length ratio), and lip thickness. Edited images of Asian models were used as references for facial aesthetic criteria in this study. Results: The survey revealed that the majority of participants were of Malay ethnicity (71.0%) and employed in the private sector (39.3%). The average age of the participants was 31.6±9.2 years, and most of them (66.9%) have not undergone aesthetic procedures before. Furthermore, a significant association was observed between ethnicity and women’s facial aesthetic preferences for facial shape and nasal width-length ratio (p<0.05). Oval facial shape was preferred by Malay (40.3%, n=83), Chinese (41.4%, n=12), and Indian (41.3%, n=19) women, due to its long, narrow, and rounded chin. For nasal width-length ratio, Malay (44.2%, n=91) and Chinese (37.9%, n=11) women preferred a ratio <1, whereas Indians (39.1%, n=18) favored a ratio >1. However, no significant association was found between ethnicity and other facial aesthetic criteria assessed in the study. Conclusion: This study identified that Malaysian women’s preferences for facial shape and nasal width-to-length ratio are associated with ethnicity. These findings can serve as a valuable reference for aesthetic practitioners, emphasizing the importance of preservation and enhancement of unique ethnic features, customized according to the suitability of each ethnicity, rather than conforming to prevailing beauty standards.